2020
DOI: 10.1186/s12885-020-07351-w
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic renal cell carcinoma patients of T4 stage who are in status of N1 stage or older than 76 years cannot benefit from cytoreductive nephrectomy

Abstract: Background: We aimed to identify which part of the patients with metastatic renal cell carcinoma (mRCC) is not suitable for cytoreductive nephrectomy (CN). Methods: The data of mRCC patients was acquired from the Surveillance, Epidemiology, and End Results (SEER) database. Multivariate cox regression analysis and nomogram were performed for selecting factors independently associated with survival. Propensity score matching (PSM) was applied to reduce potential bias when comparing survival of mRCC patients trea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Surgery is not always a viable option for patients with mRCC. For example, T4 stage mRCC patients who were in the status of N1 stage or older than 76 years, there is no difference in overall survival between cytoreductive nephrectomy and non-surgical treatment [37].…”
Section: Treatment and Prognosismentioning
confidence: 98%
“…Surgery is not always a viable option for patients with mRCC. For example, T4 stage mRCC patients who were in the status of N1 stage or older than 76 years, there is no difference in overall survival between cytoreductive nephrectomy and non-surgical treatment [37].…”
Section: Treatment and Prognosismentioning
confidence: 98%
“…In particular, pathological Grade 4 was associated with a bad prognosis, and the presence of a major organ metastasis (bone, brain, liver and lung) improved survival time. Zahng et al also showed that, in 6043 patients with mRCC, CN was not suggested as the first-line strategy in T4 patients; in particular, T4 stage, N1 and age ≥ 76 yr were important risk factors influencing CSS [48]. Faba et al reported that CN showed several benefits in young male patients with oligometastatic disease and a good performance status, while patients whose life expectancy was short, who had poor risk-IMDC (International Metastatic RCC Database Consortium), or with liver and/or bone metastases, and positive lymph nodes, in addition to sarcomatoid components, showed no benefits from CN [49].…”
Section: Selection Of Patientsmentioning
confidence: 99%